1994
DOI: 10.1080/17450399409381755
|View full text |Cite
|
Sign up to set email alerts
|

Studies on energy and nitrogen metabolism of pregnant and lactating sows and suckling piglets

Abstract: The chemical composition and the energy content of the conception products, the reproductive organs and the live weight gains or losses of pregnant and lactating sows were determined in dependence on the litter number (1, 2 and 4) and the energy supply (120, 100 and 80% of requirement recommendation) of sows as well as on the course of gestation and lactation. The results will be used as a basis for factorial derivation of requirement recommendation. The deposition of protein and energy in the conception produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
5
7
0
Order By: Relevance
“…Sagel [33] determined crude fat contents of 9.8 g/kg (fresh basis) in light piglets and 10.7 g/kg (on a fresh basis) in heavy piglets; the correlation calculated as a function of DM was 0.37. Our results agree with those of Beyer et al [31], who reported crude fat contents of 9.18-11.6 g/kg (fresh basis) and 54-63 g/kg in DM. The crude fat contents (in DM) in the present study deviated slightly upwards.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Sagel [33] determined crude fat contents of 9.8 g/kg (fresh basis) in light piglets and 10.7 g/kg (on a fresh basis) in heavy piglets; the correlation calculated as a function of DM was 0.37. Our results agree with those of Beyer et al [31], who reported crude fat contents of 9.18-11.6 g/kg (fresh basis) and 54-63 g/kg in DM. The crude fat contents (in DM) in the present study deviated slightly upwards.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Sagel [33] observed slightly higher crude protein contents (on a fresh basis) in the heavy piglets. When compared to the results of Beyer et al [31], who determined the crude protein contents in the range of 569 and 594 g/kg DM, those findings are consistent with the contents of piglets from the present study with a BW of >1.2 kg at the time of birth, but not with those of piglets <1.2 kg BW, as the crude protein content of the lighter piglets had numerically higher values.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations